Relationship Between Teacher Competence and Motivation With Student Learning Outcomes in Subjects Elementary School People in Tujuh Belas Sub District - Tarlina; Ashadi Cahyadi; Suriani Sari (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to investigate the relationship between teacher competency and motivation with student learning outcomes in the Physical Education subject in elementary schools throughout the Seventeen District. The research method is correlation research. The research sample consisted of 10 Physical Education teachers from various elementary schools in Seventeen District. Data was collected through a research instrument in the form of a questionnaire that had been tested for validity and reliability. The results showed that there was a significant positive relationship between teacher competence in teaching Physical Education subjects and student learning outcomes. Teachers who have higher competence in teaching Physical Education tend to have students with better learning outcomes. In addition, the research results also show that there is a significant positive relationship between teacher motivation in teaching Physical Education and student learning outcomes. Teachers who are highly motivated in teaching Physical Education tend to have students with better learning outcomes. This research provides important implications in the context of improving the quality of Physical Education learning in elementary schools. Teachers need to continue to develop their competence in teaching Physical Education subjects, with attention to effective and relevant teaching methods. In addition, teacher motivation also needs to be considered, so that teachers can create a learning environment that motivates students to achieve optimal learning outcomes.